Reciprocal Teaching-Learning Model Assisted with Flash Card Improve Student Science Competence - Indra Kasuma, I Gusti Ngurah Gede Agung; Ngurah Wiyasa, I Komang (Universitas Pendidikan Ganesha, 2020)
The problem that is the basis of this research is that students tend to be passive and students are more likely to talk to their peers, so the purpose of this study is to determine the effect of the reciprocal teaching model assisted by flash card media on the competence of science knowledge in fourth grade students. The type of this research is quasi-experimental using a non-equivalent control group design. The population contained in this study was 266 students. Samples were taken using a random cluster technique which then obtained an experimental class of 36 people and a control class of 31 people. Data collection for science knowledge competencies using 40 validated objective test instruments. The data obtained were then analyzed using the polled variance t-test. Based on data analysis, it was obtained tcount = 5,250> t table = 2,000 at a significance level of 5% with dk = 65, so, H0 was rejected and Ha was accepted. So it can be concluded that there is a significant influence on the reciprocal teaching model of learning assisted by flash card media on the science knowledge competence of fourth grade students. The implication of this research in general is that this model can be used as an alternative for teachers in learning activities in order to increase the competency of students' science knowledge